The Power of Language and the Language of Power: The Blue-Eyes, Brown-Eyes Workshop - Stephens, Tanne (Satura, 2022)
Oppression takes many forms, but language may be one of the most pervasive and allusive tools people use to exert their power. I was struck by this fact the day I was introduced to Jane Elliott and her famous Blue-eyes/Brown-eyes exercise in a psychology course. As an educator in the US, Elliott strove to teach her third-grade students about racism, and in 1968, she conducted an exercise in her classroom to do just that. Separating students by eye color, she created a situation where they could experience firsthand the consequences of separation and oppression – a lesson Elliott became widely known for in the United States and globally.